The Impact of E-Portfolio Assessment Implementation on Polytechnic Students’ Speaking Proficiency and Self-Reflection on Learning Business English - Qiao Liping; Salmah Anisah Abu Hassan; Xu Yiping (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
As an effective learning and assessment tool, E-portfolio has enjoyed great popularity with its great benefits in improving academic performances. However, few empirical studies have focused on integrating e-portfolio assessment into ESP courses by adopting blended learning mode. This study aims to investigate the effect of e-portfolio on students’ speaking proficiency in an ESP course within the context of blended learning and the learners’ use of self-reflection strategies. Data on students’ performance on the final speaking test, teacher observation and semi-structured interview were collected from second-year Business English students in Ningbo Polytechnics in China. The data were both qualitatively and quantitatively analysed. The findings revealed that the use of e-portfolio had a significant effect on improving students’ speaking proficiency in discourse and interactive communication. Evidence from the study also indicate that guided reflection has enabled students’ active engagement in e-portfolio development and thus their new understanding on the basis of reflection could be integrated into personal practices to help achieve learning outcomes.